Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538915
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing homework as cooperative, formative assessment

Abstract: Traditional processes for homework assignments are not always a good fit for the sorts of problems often seen in computer science classes. We present our experiences in implementing policies designed to encourage students to involve the instructor and fellow students in their learning process. By shifting to group assignments and permitting students a revision cycle, we improve student satisfaction and maintain or increase student outcomes while decreasing the instructor's grading load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In educational research, formative assessment has been cited as one of the most powerful sources to improve student learning and class engagement [7]. Such mechanisms have been implemented in prior CS teaching using a revision cycle for homework questions to improve learning outcomes [2]. However, our focus on formative assessment was designed to improve teaching; thus, we used the journal as a direct, private channel for students to inform instructors about what was good or bad, difficult or easy, interesting or boring, regarding each week's assignments and content.…”
Section: Journalsmentioning
confidence: 99%
“…In educational research, formative assessment has been cited as one of the most powerful sources to improve student learning and class engagement [7]. Such mechanisms have been implemented in prior CS teaching using a revision cycle for homework questions to improve learning outcomes [2]. However, our focus on formative assessment was designed to improve teaching; thus, we used the journal as a direct, private channel for students to inform instructors about what was good or bad, difficult or easy, interesting or boring, regarding each week's assignments and content.…”
Section: Journalsmentioning
confidence: 99%
“…Rodriguez [28] examined how pair programming and student collaboration affected learning outcomes, finding that if pair programming is done properly, collaboration increases learning and understanding. Blaheta [4] studied cooperative learning and found that students had a positive reaction. Simon [24] found that peer instruction had a positive impact on student perception of learning.…”
Section: Related Workmentioning
confidence: 99%
“…In practice, metacognitive homework strategies in engineering courses are those that encourage students to think about how they solve engineering problems. "Student-graded," "self-revised," and "dual-submission" homework methods all encourage student metacognition by requiring students to examine their work multiple times, though individual methods can vary widely in the specific ways students assess their problem solving [5]- [10]. Secondary benefits of homework methods that encourage metacognition can include decreased risks of cheating [11], [12], decreased instructor time spent grading homework assignments [12], and improved student attitudes towards homework [5], [6], though these are secondary in this study to demonstrated effects on student learning.…”
Section: Introductionmentioning
confidence: 99%